Insights into diverse performance for the electroanalysis of Pb(II) on Fe2O3 nanorods and hollow nanocubes: Toward analysis of adsorption sites. (20th October 2018) - Li, Shan-Shan; Zhou, Wen-Yi; Jiang, Min; Li, Li-Na; Sun, Yu-Feng; Guo, Zheng; Liu, Jin-Huai; Huang, Xing-Jiu
Abstract: The surface areas and the exposure of adsorption sites of nanomaterials can both affect the adsorption of heavy metal ions, and then lead to a diverse electrochemical detection response. However, it is an unsolved mystery that which one is the key factor for detection. Here, Fe2 O3 hollow nanocubes with larger surface areas and Fe2 O3 nanorods with more active adsorption sites are successfully synthesized derived from Prussian blue. The Fe2 O3 with two different morphologies are applied to modified bare electrodes that can serve as sensing interface for the electrochemical analysis of Pb(II). Interestingly, the Fe2 O3 nanorods with (010) plane, as an electrochemical sensor, are observed to be more advantageous than hollow nanocubes with (006) plane. The underlying mechanism about the diverse electrochemical performance between the two materials is sufficiently proved by Brunauer-Emmett-Teller and X-ray photoelectron spectroscopy. Remarkably, the evidences clearly suggest that a large surface area is not dominant to obtain a good analysis ability; while the exposed specific adsorption site on the surface of nanomaterials shows more determinant. Graphical abstract: Highlights: Fe2 O3 hollow nanocubes and nanorods are synthesized derived from Prussian blue. A superior sensitivity of 109.67 μA μM −1 is obtained to Pb(II) on Fe2 O3 nanorods. The response on Fe2 O3 nanorods is much better than Fe2 O3 hollow nanocubes. The different behaviors of two Fe2 O3 is due to the diversity in adsorption sites.